2019
DOI: 10.5114/wo.2019.83342
|View full text |Cite
|
Sign up to set email alerts
|

18F-fluoro-ethyl-tyrosine (18F-FET) PET/CT as a potential new diagnostic tool in multiple myeloma: a preliminary study

Abstract: Aim of the study The aim of this study was to analyse the diagnostic accuracy of “18 F-fluoro-ethyl-tyrosine ( 18 F-FET) PET/CT tracer in multiple myeloma. Material and methods The analysed group included: patients with newly diagnosed active myeloma (eight patients); in very good partial remission or complete remission (VGPR or CR) after treatment (nine patients); and with active disease after relapse (15 patients).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…An alternative AA tracer for MM imaging is [ 18 F]-FET which also showed high tumor uptake in our preclinical studies as well as in a recent clinical trial [ 8 ]. Tumor uptake of [ 18 F]-FET was, however, significantly lower than of [ 18 F]-FACBC in our preclinical study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative AA tracer for MM imaging is [ 18 F]-FET which also showed high tumor uptake in our preclinical studies as well as in a recent clinical trial [ 8 ]. Tumor uptake of [ 18 F]-FET was, however, significantly lower than of [ 18 F]-FACBC in our preclinical study.…”
Section: Discussionmentioning
confidence: 99%
“…For the AA analogue [ 18 F]-fluorethlytyrosine (FET) conflicting preclinical data about its uptake in MM cells have been reported [ 6 , 7 ]. However, a recent clinical study reported high uptake of FET by MM and excellent image contrast [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The methodology described here could potentially be adapted to compare different radiotracers recently proposed for evaluating MM, such as 11 C-choline 34 , 11 C-methionine 34 , 18 F-fluoro-ethyl-tyrosine 35 , 68 Ga-DOTATATE 36 and 68 Ga-PSMA 37 . MM lesions frequently present varying degrees of uptake of those radiotracers compared to FDG uptake 35,36 , probably due to the extensive intra and inter-patient genomic heterogeneity of the disease 38 . An objective quantitative comparison of those tracers in MM might be of interest.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study found sensitivity and specificity values of 55.58 and 9.09%, respectively, for 18 F-FET PET/CT assessment. Thus, 18 F-FET does not seem to be a promising biomarker in myeloma imaging (39).…”
Section: Clinical Value Of 11 C-met-pet In MMmentioning
confidence: 95%